Variation in eggshell traits between geographically distant populations of pied flycatchers Ficedula hypoleuca. (23rd November 2012) - Morales, Judith; Ruuskanen, Suvi; Laaksonen, Toni; Eeva, Tapio; Mateo, Rafael; Belskii, Eugen; Ivankina, Elena V.; Järvinen, Antero; Kerimov, Anvar; Korpimäki, Erkki; Krams, Indrikis; Mänd, Raivo; et al.
<x xml:space="preserve">Abstract</x> The expression and impact of maternal effects may vary greatly between populations and environments. However, little is known about large‐scale geographical patterns of variation in maternal deposition to eggs. In birds, as in other oviparous animals, the outermost maternal component of an egg is the shell, which protects the embryo, provides essential mineral resources and allows its interaction with the environment in the form of gas exchange. In this study, we explored variation of eggshell traits (mass, thickness, pore density and pigmentation) across 15 pied flycatcher populations at a large geographic scale. We found significant between‐population variation in all eggshell traits, except in pore density, suggesting spatial variation in their adaptive benefits or in the females' physiological limitations during egg laying. Between‐ population variation in shell structure was not due to geographic location (latitude and longitude) or habitat type. However, eggshells were thicker in populations that experienced higher ambient temperature during egg laying. This could be a result of maternal resource allocation to the shell being constrained under low temperatures or of an adaptation to reduce egg water loss under high temperatures. We also found that eggshell colour intensity was positively associated with biliverdin pigment concentration, shell thickness and pore density. To conclude, our findings reveal large‐ scale between‐population variation of eggshell traits, although we found little environmental dependency in their expression. Our findings call for further studies that explore other environmental factors (e.g. calcium availability and pollution levels) and social factors like sexual selection intensity that may account for differences in shell structure between populations.